Supplemental readings for educators - Scheft, Tom (Emerald Publishing Limited : Information Age Publishing, 2012)
(This is a condensed version of Inspiring Student Writers: Strategies and Examples for Teachers.)Being an educator is a wonderfully fulfilling career, but it's not for everyone. It is also, at times, a frustrating, stressful, aggravating, depressing occupation. Far too many people think working in a school is a pretty easy job--a job anybody can do, basically babysitting with plenty of vacation time thrown in.Of course the "truth" about education is elusive, and the truth about what it means to be a great educator is equally elusive. These essays, which are written by educators, offer insights into the profession and what it takes to make a positive difference in the lives of others. These chapters are offered as catalysts for reflection and discussion.